Carbon Nanotube-Based Field-Effect Transistor Biosensors for Biomedical Applications: Decadal Developments and Advancements (2016–2025) - Joydip Sengupta; Chaudhery Mustansar Hussain (Biosensors)
Advancements in carbon nanotube-based FET (CNT-FET) biosensors from 2016 to 2025 have boosted their sensitivity, specificity, and rapid detection performance for biomedical purposes. This review highlights key innovations in transducer materials, functionalization strategies, and device architectures, including floating-gate CNT-FETs for detecting cancer biomarkers, infectious disease antigens, and neurodegenerative disease markers. Novel approaches, such as dual-microfluidic field-effect biosensor (dual-MFB) structures and carboxylated graphene quantum dot (cGQD) coupling, have further expanded their diagnostic potential. Despite significant progress, challenges in scalability, reproducibility, and long-term stability remain. Overall, this work highlights the transformative potential of CNT-FET biosensors while outlining a roadmap for translating laboratory innovations into practical, high-impact biomedical applications.